2015
DOI: 10.1097/bot.0000000000000361
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal Screw Penetration With the Use of Volar Plating of Distal Radius Fractures

Abstract: Clinicians should consider use of these views to evaluate dorsal screw penetration after volar plating but may opt to subtract a few millimeters from their measured screw lengths to avoid over penetration past the dorsal cortex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 27 publications
3
29
0
Order By: Relevance
“…Two of the cadaveric studies also reported a nearly perfect interobserver agreement for the DTV (Ozer et al., 2012; Vernet et al., 2017). An important limitation of these cadaveric studies is that premade and preselected fluoroscopic images were presented to observers (Brunner et al., 2015; Hill et al., 2015; Ozer et al., 2012; Vernet et al., 2017) rather than views obtained by the observers themselves. This may explain the discrepancy between the accuracy of the cadaveric studies (Brunner et al., 2015; Joseph and Harvey, 2011; Marsland et al., 2014; Ozer and Toker, 2011) and the disappointing performance of the clinical series (Ganesh et al., 2016; Kiyak, 2018; Oc et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Two of the cadaveric studies also reported a nearly perfect interobserver agreement for the DTV (Ozer et al., 2012; Vernet et al., 2017). An important limitation of these cadaveric studies is that premade and preselected fluoroscopic images were presented to observers (Brunner et al., 2015; Hill et al., 2015; Ozer et al., 2012; Vernet et al., 2017) rather than views obtained by the observers themselves. This may explain the discrepancy between the accuracy of the cadaveric studies (Brunner et al., 2015; Joseph and Harvey, 2011; Marsland et al., 2014; Ozer and Toker, 2011) and the disappointing performance of the clinical series (Ganesh et al., 2016; Kiyak, 2018; Oc et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The fi rst (and mostly used) is with the supinated forearm inclined at 15° to the vertical X-ray beam with maximum wrist fl exion (8,12,13,21,(23)(24)(25)(26). The second is with a pronated forearm and horizontally placed fl uoroscope with the X-ray beam parallel to the dorsal aspect of the distal radius (9,27). In our study, we present the third technique, with a supinated forearm with the elbow at 90°, the wrist in maximal fl exion, and the fl uoroscope inclined at 15° to the X-ray beam.…”
Section: Discussionmentioning
confidence: 99%
“…In the cadaveric study of Hill, wrist radiographs in four planes, the 45° supination radiograph was reported to be the most sensitive to detect the dorsal cortex screw penetration [ 13 ]. In our study, we found that the dorsal tangential radiograph of the wrist was the most correlated with the USG examination.…”
Section: Discussionmentioning
confidence: 99%